A high-temperature oxidation-resistant eutectic high-entropy alloy material and a preparation method thereof
By adjusting the composition and preparation process of the eutectic high-entropy alloy, adding Ta, Cr, and Al elements, and optimizing the FCC+Laves dual-phase structure, the problem of insufficient oxidation resistance at high temperatures was solved, and the high-temperature oxidation resistance and mechanical properties were improved, making it suitable for multiple industrial fields.
Patent Information
- Application Number
- CN202410272849.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-03-11
AI Technical Summary
Eutectic high-entropy alloys have insufficient oxidation resistance at high temperatures, which limits their applications, especially since the oxidation channels of the FCC and Laves phases lead to reduced oxidation resistance.
By adjusting the alloy composition and adding Ta, Cr, and Al elements, a stable oxide film and a second strengthening phase are formed, and the alloy structure is optimized to be FCC+Laves dual-phase eutectic. The alloy is then melted in a vacuum arc melting furnace, and the melting conditions are controlled to avoid inhomogeneity, thus preparing a high-temperature oxidation-resistant eutectic high-entropy alloy.
It improves the high-temperature oxidation resistance and mechanical properties of the alloy, achieving a balance between strength and plasticity, and is suitable for shipbuilding, petrochemical, aerospace and automotive industries.
Smart Images

Figure CN118241097B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-entropy alloy preparation technology, and in particular to a high-temperature oxidation-resistant eutectic high-entropy alloy material and its preparation method. Background Technology
[0002] Eutectic high-entropy alloys (HLI) hold promise for applications in shipbuilding, petrochemicals, aerospace, and automotive industries due to their excellent mechanical properties, corrosion resistance, and good machinability. HLI compensates for the shortcomings of traditional materials in terms of mechanical properties, poor corrosion resistance, and low machinability. Furthermore, the isothermal transformation during solidification of HLI results in good fluidity, effectively preventing segregation and shrinkage cavities during casting, further facilitating their application. Among HLIs, those with a eutectic microstructure composed of both FCC and Laves phases exhibit the best mechanical properties. The FCC and Laves phases provide excellent ductility, toughness, and strength, avoiding the trade-off between strength and toughness found in traditional alloys. However, the Laves phase generally reduces the alloy's oxidation resistance. Studies have found that the Laves phase acts as an oxygen diffusion channel during alloy oxidation, promoting internal oxidation. This severely limits the high-temperature applications of FCC and Laves-phase biphase HLI. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention provides a high-temperature oxidation-resistant eutectic high-entropy alloy material and its preparation method. The eutectic high-entropy alloy material provided by this invention has the characteristics of oxidation resistance and high strength, and has good application prospects.
[0004] On one hand, the present invention provides a high-temperature oxidation-resistant eutectic high-entropy alloy material, wherein the eutectic high-entropy alloy material is composed of the following atomic percentages: Fe 34.0-38.0%, Co 21.0-23.0%, Ni 18.0-20.0%, Nb 10.0-12.0%, Al 1.0-3.0%, Ta 3.0-7.0%, and Cr 3.0-7.0%.
[0005] In one embodiment of the present invention, the eutectic high-entropy alloy material is composed of the following atomic percentages: 84.0-92.0% FeCoNiNb alloy, 2.0% Al, 3.0-7.0% Ta, and 3.0-7.0% Cr, wherein the molar ratio of each component in the FeCoNiNb alloy is: Fe:Co:Ni:Nb = 6:4:3:2.
[0006] In one embodiment of the present invention, the eutectic high-entropy alloy material has the following composition by atomic percentage: 88.0% FeCoNiNb alloy, 2.0% Al, 5.0% Ta and 5.0% Cr.
[0007] In one embodiment of the present invention, the eutectic high-entropy alloy material is an FCC+Laves dual-phase eutectic structure.
[0008] On the other hand, the present invention provides a method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material, comprising: placing Al, Ni, Co, Fe, Cr, Nb, and Ta sequentially in a vacuum arc melting furnace in a bottom-to-top order; introducing a protective atmosphere; adjusting the pressure of the vacuum arc melting furnace to a positive pressure; melting by using an electric current to induce an arc 1-3 mm above the surface of Ta, melting ≥ 3 times; and obtaining the eutectic high-entropy alloy material by suction casting.
[0009] In one embodiment of the present invention, the Al, Ni, Co, Fe, Cr, Nb, and Ta are all granular or blocky; the particle size of the Al, Ni, Co, Fe, Cr, Nb, and Ta is 1-3 mm; and the purity of the Al, Ni, Co, Fe, Cr, Nb, and Ta is greater than 99.9%.
[0010] In one embodiment of the present invention, during the melting process, the current is increased to 90-120A at a rate of 5-8A / s, and each melting process lasts for 3-4 minutes.
[0011] In one embodiment of the present invention, after any melting is completed, the cooled alloy block is flipped 180° and then melted again.
[0012] In one embodiment of the present invention, the melting process is carried out 4 to 5 times.
[0013] As can be seen from the above, the above technical solution has at least one or more of the following beneficial effects:
[0014] 1. When the alloy of the present invention has a high content of Ta and Cr, a composite oxide layer of Ta, Cr and Nb can be generated on the alloy surface to improve the oxidation resistance of the alloy. Cr can also react with oxygen to form a dense oxide layer on the alloy surface, further improving the oxidation resistance of the alloy.
[0015] 2. In the alloy of the present invention, when the Ta and Cr elements are high, the Ta and Nb elements are enriched in the Laves phase, which causes the Laves phase in the alloy to grow and improve the strength of the alloy.
[0016] 3. The properties of the eutectic high-entropy alloy of the present invention can be easily optimized by adjusting the content of elements in the alloy system.
[0017] 4. The micro Vickers hardness of the eutectic high-entropy alloy provided by this invention is 459.58–554.96 HV3. The oxidation rate can reach 2.15 × 10⁻⁶. -6 g 2 / cm 4 With a viscosity of 0.5 g / s or higher, this eutectic high-entropy alloy exhibits excellent high-temperature oxidation resistance and superior mechanical properties. The eutectic high-entropy alloy provided by this invention holds promise for applications in shipbuilding, petrochemicals, aerospace, and automotive industries.
[0018] 5. The present invention provides a method for preparing the eutectic high-entropy alloy material, which is simple and conducive to large-scale production. Attached Figure Description
[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:
[0021] Figure 1 XRD patterns of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloys in the examples and comparative examples;
[0022] Figure 2 Electron micrographs of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloys in the examples and comparative examples;
[0023] Figure 3 The oxidation curves at 900℃ of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloys in the examples and comparative examples are shown.
[0024] Figure 4 The XRD patterns of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloys in the examples and comparative examples are obtained after oxidation at 900°C for 84 hours.
[0025] Figure 5 The oxidation surface of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloy in the examples and comparative examples is shown in the image after oxidation at 900°C for 84 hours.
[0026] Figure 6 This is an oxidation cross-section diagram of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloy in the examples and comparative examples, after oxidation at 900℃ for 84 hours.
[0027] Figure 7 The room temperature compression curves of the Fe-Co-Ni-Nb-Al-Ta-Cr eutectic high-entropy alloys in the examples and comparative examples are shown. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific implementations. The following examples are implemented under the premise of the technical solutions of the present invention, providing detailed implementation methods and specific operating procedures, which will help those skilled in the art to further understand the present invention. It should be noted that the scope of protection of the present invention is not limited to the following embodiments; any adjustments and improvements made under the concept of the present invention shall fall within the scope of protection of the present invention.
[0030] All raw materials used in the embodiments of this application can be obtained from commercial channels.
[0031] This invention provides a high-temperature oxidation-resistant eutectic high-entropy alloy material, wherein the eutectic high-entropy alloy material has the following composition by atomic percentage: Fe 34.0-38.0%, Co 21.0-23.0%, Ni 18.0-20.0%, Nb 10.0-12.0%, Al 1.0-3.0%, Ta 3.0-7.0%, and Cr 3.0-7.0%.
[0032] As is well known, high-entropy alloys exhibit a unique cocktail effect, meaning that the properties of certain elements composing the alloy ultimately affect its macroscopic properties. By controlling the composition and content of eutectic high-entropy alloys, it may be possible to effectively improve the system's balance between excellent mechanical properties and high-temperature oxidation resistance. For example, adding antioxidant elements such as Ta, Cr, and Al to some high-entropy alloy systems can improve the alloy's high-temperature oxidation resistance. Similarly, adding a small amount of Al can effectively improve the alloy's mechanical properties. This is because the addition of Al leads to or promotes the formation of a second strengthening phase in the alloy, thus enhancing its mechanical properties. Furthermore, the addition of a small amount of Al can cause lattice distortion in the alloy, which also improves its mechanical properties.
[0033] This invention provides a high-temperature oxidation-resistant eutectic high-entropy alloy material based on a FeCoNiNb-based high-entropy alloy. This alloy is not only low-cost but also possesses excellent performance. Furthermore, by adding Ta, Cr, and Al, the oxidation resistance is improved while simultaneously enhancing the strength of the eutectic high-entropy alloy. The inventors discovered that Ta and Cr can form an oxide film, thereby improving the oxidation resistance of the eutectic high-entropy alloy. In addition, the addition of Al leads to or promotes the formation of a second strengthening phase in the alloy, improving its mechanical properties. Simultaneously, the addition of a small amount of Al causes lattice distortion in the alloy, which also improves its mechanical properties. This results in a balance between strength and plasticity, and excellent oxidation resistance.
[0034] Of course, the composition of this invention needs to be effectively controlled. If the Ta content is too high, the Ta element tends to accumulate in the Laves phase of the alloy, causing the Laves phase to grow excessively and promoting the disappearance of the eutectic structure. The Laves phase is beneficial for improving the strength of the alloy. However, if the content of the Laves phase structure is too high, it will lead to an increase in the strength of the alloy but a decrease in toughness. If the Ta and Cr contents are too low, the oxidation resistance of the alloy will not be significantly improved. When the Al content is too high, the addition of Al element causes large lattice expansion and high lattice distortion energy, which will promote the formation of the BCC phase. The two-phase eutectic structure in the alloy will be destroyed, and the mechanical properties of the alloy will decrease significantly. If the Al content is too low, it will not be able to strengthen the mechanical properties of the alloy.
[0035] In a preferred embodiment, the eutectic high-entropy alloy material has the following composition by atomic percentage: 84.0–92.0% FeCoNiNb alloy, 2.0% Al, 3.0–7.0% Ta, and 3.0–7.0% Cr, wherein in the FeCoNiNb alloy, the molar ratio is Fe:Co:Ni:Nb = 6:4:3:2.
[0036] In a further preferred embodiment, the eutectic high-entropy alloy material has the following composition by atomic percentage: 88.0% FeCoNiNb alloy, 2.0% Al, 5.0% Ta, and 5.0% Cr.
[0037] In a preferred embodiment, the eutectic high-entropy alloy material is an FCC+Laves dual-phase eutectic structure, wherein bulk Laves phases are distributed between the eutectic structures.
[0038] This invention discloses a method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material. Al, Ni, Co, Fe, Cr, Nb, and Ta are placed sequentially in a vacuum arc melting furnace from bottom to top. A protective atmosphere is first introduced, and the pressure of the vacuum arc melting furnace is adjusted to positive pressure. Then, an electric arc is generated by current, extending 1-3 mm above the surface of Ta for melting. The melting process is repeated ≥3 times, and the eutectic high-entropy alloy material is obtained by suction casting.
[0039] The preparation method of this invention uses a vacuum arc melting furnace. During the melting process, Al, Ni, Co, Fe, Cr, Nb, and Ta are placed in the vacuum arc melting furnace in a bottom-up order. After the vacuum arc melting furnace is brought to positive pressure, an electric arc is induced by current for melting. The electric arc induced by the current is controlled to be higher than the surface of Ta during melting. The inventors have found that, through the synergistic effect of the above-mentioned raw material placement method, pressure setting, and melting method, the high-melting-point elements can coat the low-melting-point elements after melting, which can effectively avoid the phenomenon of uneven alloy melting during the melting process.
[0040] In actual operation, after Al, Ni, Co, Fe, Cr, Nb, and Ta are placed in a vacuum arc melting furnace in sequence, they are first purged twice with argon gas and then evacuated to a vacuum of 5 × 10⁻⁶. -3 Pa, then pressurize with high-purity argon gas to a slightly positive pressure.
[0041] In a preferred embodiment, the Al, Ni, Co, Fe, Cr, Nb, and Ta are all in granular or block form.
[0042] In a preferred embodiment, the particle size of Al, Ni, Co, Fe, Cr, Nb, and Ta is 1–3 mm.
[0043] The inventors discovered that by controlling the particle size of pure metals Al, Ni, Co, Fe, Cr, Nb, and Ta within the aforementioned range, the final smelted metal has the optimal morphology and the most uniform composition.
[0044] In a preferred embodiment, the purity of Al, Ni, Co, Fe, Cr, Nb, and Ta is all greater than 99.9%.
[0045] In actual operation, before smelting, the oxide scale on the surface of Al, Ni, Co, Fe, Cr, Nb, and Ta raw materials is first removed with sandpaper. Then, the raw materials are placed in a container, and anhydrous ethanol solution is added. The mixture is then ultrasonically cleaned for 10 minutes to remove dust and oil from the surface. The anhydrous ethanol solution is replaced, and ultrasonic cleaning is performed for another 5 minutes. Finally, the raw materials are dried with a hair dryer to obtain clean Al, Ni, Co, Fe, Cr, Nb, and Ta raw materials.
[0046] The raw materials are then placed sequentially into the melting pool of the cold crucible, with the middle melting pool used to hold the titanium ingots. The circulating cooling water system is turned on, and the furnace door is closed tightly. The mechanical diffusion pump is turned on, and a vacuum of 5 × 10⁻⁶ is created. -1 Below Pa, the vacuum level is then reduced to 5 × 10 using a molecular pump. -3 Below Pa, turn off the molecular pump, mechanical pump, and valves. Open the argon filling valve and fill the furnace chamber with argon gas until the vacuum arc melting furnace reaches a slightly positive pressure. Then close the argon filling valve. Lower the electrode to 1-3 mm above the raw material to ignite the arc, then raise the electrode to about 10 mm. Adjust the current control knob to gradually increase the current for melting. Before sampling, the titanium ingot should be melted first to absorb oxygen in the furnace chamber. The alloy sample should be repeatedly turned over during melting to achieve uniform composition in the alloy. After melting, turn off the power and wait for the alloy to cool for 10 minutes. Then open the vent valve and open the furnace door to remove the button-shaped alloy ingot.
[0047] In a preferred embodiment, during the melting process, the current is increased to 90-120A at a rate of 5-8A / s, and each melting process lasts for 3-4 minutes.
[0048] The inventors discovered that the best melting effect is achieved when the current is increased to 90-120A using the above-mentioned current increase method. However, if the current increase is too fast, stress is generated in the melting sample, making the sample prone to cracking. If the current increase is too slow, the melting will be uneven.
[0049] In a preferred embodiment, after any melting is completed, the cooled alloy block is flipped 180° before the next melting.
[0050] By flipping the alloy block, the uniformity of the final eutectic high-entropy alloy material can be improved. Preferably, the melting process is repeated 4 to 5 times.
[0051] After melting, during suction casting, the sample is placed in the suction casting crucible and melted to a molten state. The straight valve is then pulled out, and the straight casting valve is quickly opened while simultaneously shutting off the melting current. In actual operation, the cooling rate must be controlled by the circulating water flow rate to prevent excessive speed, which could cause the alloy to crack.
[0052] This invention discloses a high-temperature oxidation-resistant eutectic high-entropy alloy material based on a FeCoNiNb-based high-entropy alloy, which is not only low-cost but also possesses excellent performance. By adding Al, Ta, and Cr, the strength is improved while simultaneously enhancing the high-temperature oxidation resistance of the high-entropy alloy. The inventors discovered that at high temperatures, Ta, Cr, and Nb elements in the alloy can form a stable composite oxide film, thereby improving the high-temperature oxidation resistance of the high-entropy alloy. Furthermore, the addition of a small amount of Al can lead to or promote the formation of a second strengthening phase in the alloy, improving its mechanical properties. Simultaneously, the addition of a small amount of Al causes lattice distortion in the alloy, which also improves its mechanical properties. The alloy forms an FCC+Laves phase dual-phase eutectic with a bulk Laves phase structure, resulting in enhanced strength and significantly improved oxidation resistance.
[0053] The preparation method of this invention uses a vacuum arc melting furnace. During the melting process, Al, Ni, Co, Fe, Cr, Nb, and Ta are placed in the vacuum arc melting furnace in a bottom-up order. After the vacuum arc melting furnace is brought to positive pressure, an electric arc is induced by current for melting. The electric arc induced by the current is controlled to be higher than the surface of Ta during melting. The inventors have found that, through the synergistic effect of the above-mentioned raw material placement method, pressure setting, and melting method, the high-melting-point elements can coat the low-melting-point elements after melting, which can effectively avoid the phenomenon of uneven alloy melting during the melting process.
[0054] Example 1
[0055] A Fe-Co-Ni-Nb-Al-Ta-Cr high-entropy alloy, the alloy formula is: Fe q Co x Ni y Nb z Al₂Ta₃Cr₃, where q + x + y + z = 92, has a theoretical density of 8.52 g / cm³. 3 As a more detailed example, its preparation method and related tests include the following steps:
[0056] Ingredients: 3.2695g Fe, 2.1257g Co, 1.7361g Ni, 1.7027g Nb, 0.0836g Al, 0.8409g Ta, and 0.2416g Cr raw materials with a purity ≥99.95% and a particle size of 1–3mm are selected (the above raw material weights are based on the desired yield of 10g Fe). q Co x Ni y Nb zAl2Ta3Cr3 (q+x+y+z=92) was calculated. According to the formula, the raw materials were weighed according to the proportions. Before weighing, the oxide film on the surface of the raw materials was removed by sandpaper or a grinding wheel. Then, the raw materials were placed in a beaker containing anhydrous ethanol and ultrasonically cleaned for 100 seconds, followed by complete drying with a hair dryer. The mass of each component was accurately weighed using an electronic balance with an accuracy of 0.0001g.
[0057] (2) Melting and Casting: In a non-consumable vacuum arc furnace, the metal raw materials are placed in the vacuum arc melting furnace in the following order from bottom to top: Al, Ni, Co, Fe, Cr, Nb, and Ta. After the raw materials are placed, the mechanical pump and molecular pump are turned on sequentially to evacuate the furnace until the vacuum degree reaches 5 × 10⁻⁶. -3 After the pressure reaches a certain level (Pa), argon gas is introduced for protection, and the vacuum arc melting furnace is brought to a slightly positive pressure. The arc is induced by current and extends 3 mm above the surface of Ta for melting. Before melting the alloy, Ti particles pre-placed in the furnace are melted to consume free oxygen. During melting, the current is increased to 100 A at a rate of 6 A / s, and each melting session lasts 4 minutes. After the alloy cools, it is turned over, and this process is repeated 5 times to ensure thorough and uniform melting. After melting, the alloy is cast into a copper mold.
[0058] (3) The alloy ingot is then cut into rectangular blocks of 1.5mm×3mm×6mm by wire EDM. After coarse grinding, fine grinding, polishing, cleaning and drying, a clean sample that meets the experimental requirements is obtained.
[0059] (4) Place the clean sample in a clean corundum crucible and place them together in a tube furnace for oxidation at 900°C.
[0060] The Fe obtained in this example q Co x Ni y Nb z The XRD pattern of the Al2Ta3Cr3 (q+x+y+z=92) high-entropy alloy is shown below. Figure 1 As shown; the as-cast alloy consists of an FCC and Laves phase structure, as... Figure 2 (b) shows the high-temperature oxidation curve. Figure 3 As shown, the alloy oxidation effect is good; the XRD pattern after 84 hours of oxidation is shown below. Figure 4 As shown, oxides of Ta and Cr, oxides of Nb and Cr, oxides of Cr, and oxides of Fe are formed; the oxidized surface after 84 hours of oxidation is as follows. Figure 5 As shown in (b), the oxide particles on the alloy surface are small, and the oxide layer is dense; the oxide cross section after 84 hours of oxidation is shown in Figure 1. Figure 6 As shown in (b), the oxide exhibits stratification. The room temperature compression curve of the alloy is shown below. Figure 7 As shown, the alloy yield strength reaches 1550 MPa, and the deformation rate is about 10%.
[0061] Example 2
[0062] A Fe-Co-Ni-Nb-Al-Ta-Cr high-entropy alloy, the alloy formula is: Fe q Co x Ni y Nb z Al2Ta5Cr5(q+x+y+z=92) has a theoretical density of 8.66 g / cm³. 3 As a more detailed example, its preparation method and related tests include the following steps:
[0063] The preparation method of Example 2 is roughly the same as that of Example 1, except that:
[0064] (1) Ingredients: 3.0252g Fe, 1.9669g Co, 1.6064g Ni, 1.5755g Nb, 0.0809g Al, 1.3557g Ta and 0.3896Cr raw materials with a purity ≥99.95% were selected;
[0065] (3) Fe obtained in this example q Co x Ni y Nb z The XRD pattern of the Al2Ta5Cr5 (q+x+y+z=92) high-entropy alloy is shown below. Figure 1 As shown, with the increase of Ta and Cr elements, the Laves peak gradually strengthens, while the FCC peak gradually weakens; the as-cast alloy consists of an FCC and Laves phase structure, as shown in the figure. Figure 2 As shown in (c); the high-temperature oxidation curve is as follows: Figure 3 As shown, the alloy oxidation effect is further improved, indicating that the addition of Ta and Cr can improve oxidation resistance; the XRD pattern after 84 hours of oxidation is shown in the figure. Figure 4 As shown, oxides of Ta and Cr, oxides of Nb and Cr, oxides of Cr, and oxides of Fe are formed; the oxidized surface after 84 hours of oxidation is as follows. Figure 5 As shown in (c), the oxide layer on the alloy surface is dense, and the oxide particles show agglomeration; the oxide cross section after 84 hours of oxidation is shown in Figure 1. Figure 6 As shown in (c), the oxide still exhibits delamination. The room temperature compression curve of the alloy is shown below. Figure 7 As shown, the alloy yield strength reaches 1600 MPa, and the deformation rate is about 10%.
[0066] Example 3
[0067] A Fe-Co-Ni-Nb-Al-Ta-Cr high-entropy alloy, the alloy formula is: Fe q Co x Niy Nb z Al2Ta7Cr7(q+x+y+z=84) has a theoretical density of 8.8 g / cm³. 3 As a more detailed example, its preparation method and related tests include the following steps:
[0068] The preparation method of Example 3 is roughly the same as that of Example 1, except that:
[0069] (1) Ingredients: 2.7964g Fe, 1.8181g Co, 1.4849g Ni, 1.4563g Nb, 0.0783g Al, 1.8379g Ta and 0.5281Cr raw materials with a purity ≥99.95% were selected;
[0070] (3) Fe obtained in this example q Co x Ni y Nb z The XRD pattern of the Al2Ta7Cr7 (q+x+y+z=84) high-entropy alloy is shown below. Figure 1 As shown, with the increase of Ta and Cr elements, the peak of the Laves phase gradually strengthens, while the peak of the FCC phase gradually weakens; the as-cast alloy consists of an FCC and Laves phase structure, as shown in the figure. Figure 2 As shown in (d); the high-temperature oxidation curve is as follows. Figure 3 As shown, the oxidation effect of the alloy is further improved, indicating that the addition of Ta and Cr elements can improve oxidation resistance; the XRD pattern after 84 hours of oxidation is shown in the figure. Figure 4 As shown, oxides of Ta and Cr, oxides of Nb and Cr, oxides of Cr, and oxides of Fe are generated; the oxide surface after 84 hours of oxidation is as follows. Figure 5 As shown in (d), the oxide layer is dense, and the oxide particles are the largest agglomerates.
[0071] The oxidation cross section after 84 hours of oxidation is as follows Figure 6 As shown in (d), the oxide still exhibits stratification. The room temperature compression curve of the alloy is shown in... Figure 7 As shown, the alloy yield strength is only 1480 MPa, and the deformation rate is only about 8%.
[0072] Comparative Example 1
[0073] A Fe-Co-Ni-Nb-Al high-entropy alloy, the alloy formula is Fe q Co x Ni y Nb z Al2(q+x+y+z=98) has a theoretical density of 8.32 g / cm³. 3 As a more detailed example, its preparation method and related tests include the following steps:
[0074] The preparation method of Comparative Example 1 is roughly the same as that of Example 1, except that:
[0075] (1) Ingredients: 3.6684g Fe, 2.3851g Co, 1.9480g Ni, 1.9105g Nb and 0.0880g Al raw materials with a purity ≥99.95% were selected;
[0076] (3) Fe obtained in this example q Co x Ni y Nb z The XRD pattern of the Al2(q+x+y+z=98) high-entropy alloy is shown below. Figure 1 As shown, the as-cast alloy consists of FCC and Laves phase structures, such as Figure 2 As shown in (a); the high-temperature oxidation curve is as follows Figure 3 As shown, the alloy has extremely poor oxidation resistance; the XRD pattern after 84 hours of oxidation is shown in the figure. Figure 4 As shown, Fe oxide is generated; the oxidized surface after 84 hours of oxidation is as follows. Figure 5 As shown in (a), only Fe oxide was found on the alloy surface, and the oxide crystal structure was obvious; the oxidation cross section after 84 hours of oxidation is shown in Figure 1. Figure 6 As shown in (a), the oxide exhibits stratification, with the outer layer consisting solely of Fe oxide. The room temperature compression curve of the alloy is shown below. Figure 7 As shown, the alloy yield strength reaches 1500 MPa, and the deformation rate is about 10%.
[0077] Comparative Example 2
[0078] Under the same conditions as in Example 1, a Fe-Co-Ni-Nb-Al-Ta-Cr high-entropy alloy was obtained. The alloy's formula is Fe q Co x Ni y Nb z Al2Ta9Cr9(q+x+y+z=80) was prepared using the same method as in Example 1. Subsequently, an oxidized sample was prepared by wire cutting and an oxidation experiment was conducted. It was found that the antioxidant performance was not significantly improved, but the mechanical properties were extremely poor.
[0079] Comparative Example 3
[0080] Other conditions were the same as in Example 1, with argon gas filling for protection and the vacuum arc melting furnace kept at atmospheric pressure. Oxidation samples were then prepared by wire cutting, and it was found that the alloy was not uniform. An oxidation experiment was conducted, and the oxidation rate was nearly two orders of magnitude lower.
[0081] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
[0082] Furthermore, it is understood that the foregoing embodiments are merely illustrative examples of the present invention. Provided that the technical features do not conflict, the structure is not contradictory, and the purpose of the invention is not violated, the technical solutions of the various embodiments can be arbitrarily combined and used.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-temperature oxidation-resistant eutectic high-entropy alloy material, characterized in that, The eutectic high-entropy alloy material has the following composition by atomic percentage: Fe 34.0~38.0%, Co 21.0~23.0%, Ni 18.0~20.0%, Nb 10.0~12.0%, Al 1.0~3.0%, Ta 3.0~7.0% and Cr 3.0~7.0%.
2. The high-temperature oxidation-resistant eutectic high-entropy alloy material according to claim 1, characterized in that, The eutectic high-entropy alloy material has an FCC+Laves dual-phase eutectic structure.
3. A method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material, used to prepare the eutectic high-entropy alloy material as described in any one of claims 1-2, characterized in that, include: Al, Ni, Co, Fe, Cr, Nb, and Ta are placed in the vacuum arc melting furnace in the order from bottom to top. A protective atmosphere is introduced; Adjust the pressure of the vacuum arc melting furnace to positive pressure; Melting is carried out by induced electric arc by current, which is 1-3 mm above the surface of Ta, and the number of melting times is ≥3. Eutectic high-entropy alloy materials were obtained by suction casting.
4. The method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material according to claim 3, characterized in that, The Al, Ni, Co, Fe, Cr, Nb, and Ta are all in granular form; The particle size of Al, Ni, Co, Fe, Cr, Nb, and Ta is 1–3 mm. The purity of Al, Ni, Co, Fe, Cr, Nb, and Ta is all greater than 99.9%.
5. The method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material according to claim 3, characterized in that, During the melting process, the current is increased to 90-120A at a rate of 5-8A / s, and each melting session lasts for 3-4 minutes.
6. The method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material according to claim 3, characterized in that, After any melting is completed, the cooled alloy block is flipped 180° and then melted again.
7. The method for preparing a high-temperature oxidation-resistant eutectic high-entropy alloy material according to claim 3, characterized in that, The melting process is repeated 4 to 5 times.
Citation Information
Patent Citations
High-strength corrosion-resistant nickel-base superalloy and manufacturing method thereof
CN108384992A
Nickel-iron-rich low-cobalt high-strength double-phase nickel-based alloy and preparation method thereof
CN115094273A
